Avaliação da halitose em indivíduos adultos após tratamento com terapia fotodinâmica: estudo randomizado, controlado com 3 meses de acompanhamento - Romero, Sergio dos Santos (2020)
The prevalence of halitosis has increased in recent years. Although antimicrobial photodynamic therapy (aPDT) is very effective in eliminating halitosis, it returns a week after treatment. This probably occurs because bacteria residing in the oral cavity can recolonize the back of the tongue. This randomized controlled clinical trial aimed to treat oral halitosis with aPDT or scraper in healthy adults with a 7-day and 3-month follow-up followed by oral hygiene guidance. This study was approved by the UNINOVE Ethics Committee (nº 3,257,104) and registered at www.clinicaltrial.gov (NCT 03996915). Participants with positive halitosis were randomized into two groups: G1 (experimental) - treatment with aPDT in the posterior third of the tongue (in the region of the lingual tongue) and G2 (control) - lingual scraper (back of the tongue). All individuals received guidance on oral hygiene (OHB). Halitosis was evaluated by measuring volatile sulfur compounds: hydrogen sulfide (H2S), methylmercaptan (CH3SH) and dimethyl sulfide (CH3SCH3) by gas chromatography. Positive halitosis > 112ppb (hydrogen sulfide gas) was considered. The variables were assessed at baseline, 7 and 90 days. The impact of oral health related to quality of life was assessed using the OHIP-14 questionnaire (baseline and 90 days). The aPDT group was as effective in decreasing hydrogen sulfide as the scraper group immediately after treatment. There was no difference between groups immediately after treatment (p = 1532) after 7 days (p = 0.9312) and after 90 days (p = 0.6642). For the PDT group, there was a decrease in hydrogen sulfide values immediately after treatment (p = 0.0001), after 1 week there was a return of halitosis, but compared to baseline the values remained lower (p = 0.0088). The same occurred after 3 months (p = 0.0270). For the Scraper group, there was a decrease immediately after treatment (p = 0.0001), an increase after 7 days (positive halitosis) but they remained in low level when compared to the initial values (p = 0.0003), the same occurring at 3 months (p = 0.0001). For mercaptan and dimethyl sulfide, there was no change in values after treatments (p <0.05) for any of the analyzed times. For total OHIP scores and domain scores, no difference was found (p> 0.05) between groups at any time. Therefore, aPDT and the tongue scraper showed good results when associated with oral hygiene guidance. There was no perception of the impact of oral health on the quality of life of the patients evaluated.